Cortical motor threshold determination in dogs. (June 2019) - Dockx, R.; Baeken, C.; Vlerick, L.; Bhatti, S.F.M.; Polis, I.; Van Laeken, N.; Van Ham, L.; De Vos, F.; Saunders, J.H.; Peremans, K.
Abstract: In humans, determining the cortical motor threshold (CMT) is a critical step in successfully applying a transcranial magnetic stimulation (TMS) treatment. Stimulus intensity, safety and efficacy of a TMS treatment are dependent of the correct assessment of the CMT. Given that TMS in dogs could serve as a natural animal model, an accurate and reliable technique for the measurement of the CMT should be available for dogs. Using a visual descending staircase paradigm (Rossini paradigm), the CMT repeatability was assessed and compared to the electromyographic (EMG) variant. The influence of a HF-rTMS treatment on the CMT was examined. Subsequently, the CMT was measured under sedation and general anaesthesia. Finally, the coil-cortex distance was associated with the CMT, weight, age and gender. During one year the CMT was measured three times, during which it remained constant, although a higher CMT was measured (40% higher machine output) when using EMG ( P -value < .001) and under general anaesthesia ( P -value = .005). On average, a 40% and 12% higher machine output were registered. An aHF-rTMS protocol does not influence the CMT. Males have on average a 5.2 mm larger coil cortex distance and an 11.81% higher CMT. The CMT was positively linearly associated ( P -value < .05) with the weight and age of the animals. Only within female subjects, a positive linear association was found between the CMT and the coil-cortex distance ( P -value = .02). Using the visual Rossini paradigm, the CMT can be reliably used over time and during a TMS treatment. It has to be kept in mind that when using EMG or assessing the CMT under general anaesthesia, a higher CMT is to be expected. As in humans, every parameter that influences the coil-cortex distance may also influence the CMT. Highlights: The motor threshold (CMT) is individual and easily influenced. Assessing the CMT is crucial prior to transcranial magnetic stimulation. The CMT remains constant over time and is lowered by general anaesthesia. Male dogs have a higher CMT and coil-cortex distance in comparison to female dogs. A dog's CMT is positively associated with its coil-cortex distance.